2010
DOI: 10.1182/blood-2010-01-264689
|View full text |Cite
|
Sign up to set email alerts
|

Genomic deletion of the whole IgH 3′ regulatory region (hs3a, hs1,2, hs3b, and hs4) dramatically affects class switch recombination and Ig secretion to all isotypes

Abstract: IntroductionThe immunoglobulin heavy chain locus (IgH) undergoes multiple changes along B-cell differentiation, affecting transcription and accessibility to V(D)J or class switch recombination (CSR). The iE enhancer upstream of C mostly promotes V(D)J recombination, 1 whereas IgH 3ЈRR enhancers (hs3a, hs1,2, hs3b, and hs4) have controversial roles. A role in CSR was suggested by replacing mouse hs1,2 with a neomycin resistance gene, thus affecting germline transcription and CSR to ␥2a, ␥2b, ␥3, and ⑀. 2 Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
212
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 133 publications
(227 citation statements)
references
References 13 publications
13
212
0
2
Order By: Relevance
“…We confirmed that splenocytes from 3 0 RR-deficient mice showed a dramatically reduced ability to secrete IgG 1 in vitro in response to LPS þ IL4 (Fig. 1a), which likely results from both decreased CSR in B-cells and the known defect of Ig secretion in plasma cells from such mice 6 . Parallel flow cytometry experiments evaluating membrane IgG 1 expression in B-cells confirmed that the deletion of the 3 0 RR did not abolish but reduced by 490% in vitro IgG 1 CSR (Fig.…”
Section: Resultssupporting
confidence: 72%
See 4 more Smart Citations
“…We confirmed that splenocytes from 3 0 RR-deficient mice showed a dramatically reduced ability to secrete IgG 1 in vitro in response to LPS þ IL4 (Fig. 1a), which likely results from both decreased CSR in B-cells and the known defect of Ig secretion in plasma cells from such mice 6 . Parallel flow cytometry experiments evaluating membrane IgG 1 expression in B-cells confirmed that the deletion of the 3 0 RR did not abolish but reduced by 490% in vitro IgG 1 CSR (Fig.…”
Section: Resultssupporting
confidence: 72%
“…The IgG 1 class displays a special status with regard to 3 0 RR mutations, since it was the only Ig class whose expression was preserved after the first reported partial 3 0 RR alterations or truncations 17,18 . Even after complete deletion of the 3 0 RR, while CSR to all other class-switched Ig was nearly abolished, residual low-level CSR to IgG 1 was maintained 6 . We thus now take advantage of this preserved IgG 1 switching in 3 0 RR-deficient mice to explore whether it reveals additional 3 0 RR-dependent mechanistic features during CSR.…”
mentioning
confidence: 98%
See 3 more Smart Citations